An Introduction to Hybrid Machining Technology - Ahmed, Anwer; Verma, Sushant; Kumar Sharma, Vipul; Gupta, Anuj (International Journal of Engineering and Technology, 2018)
Now recent research and development are focused on the combination of two or more machining method for difficult â€“to â€“machine materials, by which the limitations of one process can be resolved by another one and at the same time can take the benefits of other methods. Such kind of combination of machining process is called Hybrid Machining Processes (HMPs). This paper covers the different HMPs and their development.Â